The molecular mechanism of ambrosin-induced cytotoxicity of human breast cancer and bladder cancer cells - El-Sawy, Layla; Rubin, John R.; Broses, Luke; Patsalis, Christopher; Henderson, Marian L.; Wilson, Steven J.; Glase, Shelly A.; Munson, Katherine A.; Hiles, Guadalupe Lorenzatti; Cates, Angelica; Emamdjomeh, Amir; Chou, Andrew; et al. (The Journal of biological chemistry, 2025)
Sesquiterpene lactones (STL) are lipophilic compounds synthesized as secondary metabolites in species across the plant kingdom, most notably in the family Asteraceae. One STL, found in North African Ambrosia maritima (A. maritima), and Caribbean Ambrosia hispida (A. hispida), is the compound ambrosin. We have extracted ambrosin from A. maritima and A. hispida and demonstrated its toxicity in bladder cancer and breast cancer cell lines at low micromolar concentrations. Ambrosin also inhibited bladder cancer and breast cancer stem cell growth as non-adherent tumor spheroids. Sequencing of ambrosin-induced synthesis of nascent RNA revealed mitochondrial apoptotic gene signatures as well as activation of glutathione metabolism, indicating the generation of reactive oxygen species (ROS). Ambrosin exhibited antagonistic activity against EGFR tyrosine kinase and RhoC GTPase. Further studies showed that ambrosin inhibited EGFR auto-phosphorylation at tyrosine 1068 (Y1068) as well as the inhibition of RhoC GTPase activity. These findings indicate novel mechanisms of action and justify further considerations for the development of ambrosin as a potential agent for advanced bladder cancer and advanced breast cancer.